THREE-STAGE SYNCHRONOUS OVERMODULATION CONTROL OF FIVE-PHASE INVERTERS - Oleschuk V.; Griva R.; Prudeak R.; Sizov A. (Problems of the Regional Energetics)
Novel three-stage algorithm of synchronous PWM control of five-phase inverter in the zone of overmodulation has been proposed and investigated. It provides smooth transition from linear modulation range to the ten-step operation mode of five-phase system at the maximum fundamental frequency, with full DC-bus voltage utilization. Simulations give the behavior of five-phase system during synchronous PWM control in the zone of overmodulation.